Morphometric Blastocyst Assessment: A Retrospective Study Examining the Relationship Between Blastocyst Diameter and Area and Pregnancy Outcomes in Assisted Reproduction Technology Cycles - Sciorio, Romualdo; Greco, Pier Francesco; Tramontano, Luca; Gullo, Giuseppe; Greco, Ermanno (Journal of clinical medicine, 2025)
Objective: In assisted reproductive technology (ART), achieving a successful pregnancy requires optimizing an embryo culture and selecting the single embryo with the highest implantation potential, capable of resulting in a healthy pregnancy. The primary goal of this study was to determine the correlation between the blastocyst area and diameter and pregnancy outcomes in ART treatments. Methods: In this study, the blastocyst diameter and area were measured to determine whether these morphometric features could predict pregnancy outcomes in couples undergoing ART with ICSI. This is a retrospective trial analyzing 665 patients who underwent an ART cycle with the transfer of a single blastocyst on day 5. Results: Both morphometric features assessed were significantly associated with implantation and ongoing pregnancy outcomes. Our results showed that the implantation rate (IR) and ongoing clinical pregnancy rate (CPR) were significantly higher with a blastocyst area ≥ 25,000 µm2 compared to <25,000 µm2 (IR: 69.8% versus 47.9%, p < 0.001; CPR: 65.5% versus 45.9% p < 0.001). Additionally, a blastocyst diameter ≥ 170 µm resulted in a significantly higher IR and CPR compared to embryos with a diameter < 170 µm (IR: 68.8% versus 36.6%, p < 0.001; CPR: 66.3 versus 35.7%, p < 0.001). Conclusions: Blastocyst morphometric variables, being objective and measurable, are not subject to intra-operator variability and may serve as promising predictors of embryo viability and ongoing pregnancy success. These morphometric assessments could assist embryologists in selecting the embryo with the highest implantation potential from a cohort, as well as identifying those with a reduced chance of generating a successful pregnancy.